Persepsi Peternak Sapi Terhadap Pencegahan Kejadian Penyakit Jembrana Di Kecamatan Muara Papalik Kabupaten Tanjung Jabung Barat - Evry D.K Br Munthe; Nahri Idris; Sarwo Edy Wibowo (CV. SINAR HOWUHOWU, 2026)
Jembrana disease is an infectious disease that causes significant economic losses in Bali cattle farming. Muara Papalik District in West Tanjung Jabung Regency has a large Bali cattle population; therefore, farmers' understanding of disease prevention measures is crucial for maintaining livestock productivity. This study aimed to identify farmer characteristics and analyze the factors influencing their perceptions regarding Jembrana disease prevention. Data were collected via a questionnaire survey and analyzed using descriptive statistics and multiple linear regression. The results showed that the majority of farmers had an elementary school education (38.2%), 2–5 years of farming experience (61.8%), and a herd size of 5–10 cattle (61.8%). Farmers' knowledge of Jembrana disease was low; 50% were unfamiliar with the disease, and 79.4% had never attended extension programs. Farmers' perceptions regarding Jembrana disease prevention were rated as reasonably good, with an average score of 60.16%. Regression analysis yielded an R² value of 0.657, revealing that farming experience (Sig = 0.011) and knowledge level (Sig = 0.001) significantly influenced farmers' perceptions. In conclusion, greater farming experience and higher levels of knowledge correlate with more positive perceptions regarding Jembrana disease prevention. Enhancing farmer capacity through continuous education and extension services is necessary to strengthen awareness and the implementation of preventive measures in the field.